A comparative study on traditional teaching with integrated teaching on II MBBS students - Priyanka, Aluri Anjana; Vasavi, Gedela (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The term integration in education means coordination in the teaching–learning activities to ensure the harmonious functioning of the educational processes. Methods: Study was conducted in ASRAM medical college. 140 students of II MBBS were randomised into 2 groups. One group was taught by traditional didactic lecture. Other group was taught by integrated teaching along with the pathology department. A post-test questionnaire was given 3 days after the end of each session. The effectiveness of the study was done by assessing both the questionnaires. Feed-back was taken from the students on both types of teaching. Results: In Integrated teaching group, 12% got more than 80% marks, 71% got more than 60-80% marks, 11% students scored 50-60% marks and 4.7% students scored less than 50% marks. In didactic teaching group, 8.95% scored more than 80% marks, 45% students scored 60-80% marks, 23.88% students scored 50-60% marks and 14.92% students scored less than 50% marks. In our study, students felt that integrated teaching was of more useful to them. It helped them in understanding of concepts and maintaining interest in topic. They felt that there was a positive interaction which helped them to correlate the two subjects. Conclusions: This study concludes that integrated teaching is more helpful to students in learning.